An integrative framework of stakeholder engagement for innovation management and entrepreneurship development - Leonidou, Erasmia; Christofi, Michael; Vrontis, Demetris; Thrassou, Alkis (My University, 2020)
This article is the first to consolidate the state of scholarly research on stakeholder engagement in innovation management and entrepreneurship development. We hereby systematically review the relevant literature published over the past 27 years, and we integrate the various prominent research perspectives into a preliminary, multi-dimensional and integrative framework of stakeholder engagement; thus, interlinking the antecedent role of stakeholder engagement for innovation management and subsequent entrepreneurship development. Through this methodologically systematic review and framework development, we provide a more comprehensive and deeper understanding of the interaction between entrepreneurs and the various stakeholders, for enhancing innovation management and entrepreneurship development. In so doing, we consequently identify various research gaps and prescribe effective avenues for future works in this research stream. Conclusively, we discuss the implications of the stakeholder management perspective for the theory and the practice of entrepreneurship.
Keywords: Conceptual framework; Entrepreneurship development; Innovation management; Stakeholder engagement; Systematic review